Developing Serious Video Games for Data Communication Courses - Dewi Sulistiyarini; Dochi Ramadhani; Sabirin, Febrianto (JTP - Jurnal Teknologi Pendidikan, 2021)
The development of educational games for data communication courses aims to help students understand data communication subject matter. The research method used in the development of educational games for the Data Communication course is Research and Development (R&D) with the DDD-E development model. The instruments used in the development of educational games are documentation and questionnaires. The research subjects consisted of 2 media experts, 2 material experts, 2 linguists and 30 potential users. The test results show that the educational games for the data communication course get good categories from media experts, material experts, and linguists, while the responses of potential users get very good categories.